158 A Rare Case of Small B-Cell Neoplasm in the Background of Lymphoplasmacytic Lymphoma. (11th January 2018) - Reddy, Amit; Poosarla, Teja; Kaur, Jaswinder; Lam, John; Chastain, Elizabeth
Abstract: Waldenström macroglobulinemia (WM) is an IgM-secreting lymphoplasmacytic lymphoma (LPL). Other B-cell neoplasms, especially chronic myeloid leukemia and marginal zone lymphoma, show morphologic, clinical, and immunophenotypic overlap with LPL. We report a case of a 68-year-old man on immunosuppressive therapy after renal transplantation presenting with worsening renal function for eight months. His recent metabolic panel revealed an elevated total protein and a globulin gap. Laboratory results included an abnormal IgM lambda spike (2.72 g/dL) on serum electrophoresis, increased beta-2 microglobulin (7.4 mg/L), and increased serum IgM (4, 066 mg/dL). Bone marrow biopsy revealed hypercellularity with several paratrabecular and interstitial lymphoid aggregates with associated plasma cells comprising 20%-30% of the marrow. The plasma cells showed a predominance of lambda light chains by in situ hybridization. Flow cytometric analysis identified two abnormal B-cell populations. The first population ( 3% of total events) expressed CD19 and variable CD20 with lambda light chain restriction, and negative CD10, CD5, CD23, and CD38 staining. The second minute population ( 1.3% of events) was negative for surface light chains expressed CD5, CD19, CD20, and CD23. Molecular testing for MYD88 L265P was positive within the aspirate sample. Karyotype analysis showed a normal male chromosome complement (46XY). Myeloma FISH panel detected no abnormalities. The morphologic features, immunohistochemistry (IHC) staining, flow cytometry, and MYD88 L265P mutation by molecular testing, along with increased IgM lambda and beta-2 microglobulin are most consistent with a diagnosis of LPL/WM. The small population of CD19- and CD5-positive B-cells by flow cytometry and IHC represents a small monoclonal B-cell lymphocytosis. MYD88 L265P demonstrates a high clinical sensitivity and specificity for LPL but has rarely been associated with other B-cell neoplasms. In this case, the smaller clonal B-cell population represents a second accompanying neoplasm, but less likely represents a clone derived from the predominant LPL disease.